Influence of fatigue, stress, muscle soreness and sleep on perceived exertion during submaximal effort - Haddad, M.; Chaouachi, A.; Wong, D. P.; Hambli, M.; Hue, O.; Chamari, K. (Physiology & Behavior, 2013)
The aim of this study was to assess the effects of the Hooper's Index variations (i.e., self-ratings of fatigue, stress, delayed onset muscle soreness (DOMS), and sleep) on rating of perceived exertion during a 10 min submaximal exercise training session (RPE-10 min) and then check the stability and the internal consistency of RPE-10 min. Seventeen junior soccer players took part in this study. The individual Hooper's indices taken before each training session were correlated with RPE-10 min during a constant intensity and duration effort (10 min) using Pearson product moment correlation. Intraclass correlation (ICC) was used to assess the internal consistency of the RPE-10 min. All individual correlations between RPE-10 min and quality of sleep and quantity of fatigue, stress, and DOMS were non-significant (p>0.05). No significant correlations were resulted between RPE-10 min and Hooper's Index in all athletes. The ICC of RPE-10 min was 0.77 thus demonstrating internal consistency. The results of the present study demonstrated the objectivity and utility of RPE as a psychological tool for monitoring training during traditional soccer training. Therefore, the results of the present study suggest that fatigue, stress, DOMS and sleep are not major contributors of perceived exertion during traditional soccer training without excessive training loads. It seems that psychobiological factors other than fatigue, stress, DOMS and sleep may have mediated the 10 min exercise perceptual intensity.